The Impact of Integrated Reporting Practices on the Firm Value of Insurance Companies in Sri Lanka:Analysis of Moderating Effect of External Financing - Imesha, B. Achila; Gunasekara, A.L. (Department of Finance, Faculty of Commerce and Management Studies University of Kelaniya Sri Lanka, 2024)
Introduction: The aim of this study is to evaluate the impact of integrated reporting practices on the firm value in insurance companies in Sri Lanka by analyzing the moderating effect of external financing. Methodology: This study use data of 13 Insurance Companies from 2015 to 2022.The study conducted by using panel regression analysis. The data was obtained from the published annual financial reports of the sampled insurance companies. IR was measured by using content analysis and Tobin’s Q as a proxy for firm value. Findings: The results of the regression analysis revealed that IR positively and significantly effects the firm value in insurance companies in Sri Lanka while supporting the findings of the prior literature. When it is higher the disclosure level of IR company, it will earn a relatively higher firm value. Conclusion: The paper concluded that the IR effects the firm value in Insurance companies in Sri Lanka.
Keywords: Integrated Reporting, Firm Value, External Financing